Maternity Care Services in Different Countries - Kõosaar, Eliise; Kaasik-Aaslav, Urve; Siimer, Õilme; Kotkas, Ene (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: In the 21st century, it became common that people move from one country to another with the intentions of settling permanently or temporarily in the new location. At the same time, the number of asylum applicants and refugees is increasing in Europe. For example, based on data from 2014, 302 772 Ukrainian, 169 657 Chinese, 134 881 Indian and more than 75 000 Syrian citizens have got residence permits. 44,1 million (6%) of European general population are Muslims. This requires culturally sensitive midwifery and maternity care provided by health professionals to a woman giving birth, knowledge of different religious beliefs and skills to solve ethical problems caused by communication with patients having different cultural and religious needs. Objective: To develop a literature review about maternity care in Syria, Turkey, China, Israel, India, Afghanistan and Ukraine. Methods: Qualitative research method has been used, a literature review has been developed. Conclusions: In different countries, people believe in various birth rituals and it is often when maternity care is provided by an attendant having no special training. For instance, in China, women giving birth are not recommended to be touched and care providers have to give a reason for each touch. In India, a thing helping protect against the „evil eye“ has to be in a delivery room. Women in Eastern Turkey feel embarrassed at being naked during childbirth, especially when care is provided by a male one, and mostly the women give birth at home. According to Turkish beliefs, the sacred book Quran has to be in the room where a woman giving birth is. In Afganistan, in order to have midwifery care, the husband`s or some male relative`s permission is required. In Syria, women often are not satisfied by forced measures in maternity care services, for instance enema is given before labour, and having any direct indications, labour induction is done.Health care services for all citizens in Ukraine are free of charge. Mostly, women give birth in hospitals where routine procedures are performed according to orders of personnel, ignoring wishes of women giving birth. Today, in these countries maternity care services in health care institutions are provided under instruction of experienced personnel. Thus, culturally appropriate maternity care is expected, if possible.